The Importance of Communicative Competence Assessment and Measurement in Language Teaching and Learning - Sumawartini, Sumawartini; Septiyana, Himayatinnisa (Jurnal Ilmiah Profesi Pendidikan, 2024)
The concept of communicative competence and recent issue on this specific language is explored here, with the emphasis on the assessment and measurement of communicative competence from language teaching objective. Several assessment methods and research on the communicative competence is presented as well. Relating the theoretical context to the conceptual issues in learning and teaching of English as second language, it is revealed that there has been many methods and strategies used by researchers in order to measure learners’ communicative competence. Furthermore, among the four competences categories, grammatical competence is revealed to be assessed most frequently. The assessment of communicative competence help learner to activate their learning to communicate effectively in real-life social interaction when situated to the context of language teaching. With basic knowledge of communicative competence, the learners will be able to function effectively in communication within the society. Hence, educators are challenged to redesign the teaching context where all types of communicative competence can be adequately taught and measured to give learners knowledge and learning experience on communicative competence as this is one of the salient skills in learners’ lives.